Sense of Coherence and Health. The Construction of an Amendment to Antonovsky's Sense of Coherence Scale (SOC II) - Trine Flensborg-Madsen; Søren Ventegodt; Joav Merrick (The Scientific World Journal)
In two previous papers, we concluded that (1) the sense of coherence (SOC) scale developed by Aaron Antonovsky (1923—1994) is unable to prove the association between SOC and the physical health empirically and (2) the SOC scale is unlikely to be a fair materialization of Antonovskys idea and, thus, unlikely to measure SOC correctly. In order to improve the scale, we developed some new questions that we suggest should be incorporated in a new questionnaire and scale (SOC II) derived directly from Antonovsky's idea and the three key explanatory concepts of SOC: comprehensibility, manageability, and meaningfulness. We hope that this new scale will demonstrate a stronger correlation between SOC and physical health.